Sap flow characteristics and responses to summer rainfall for Pinus tabulaeformis and Hippophae rhamnoides in the Loess hilly region of China. Issue 1 (3rd December 2017) - Wu, Xu; Tang, Yakun; Chen, Yunming; Wen, Jie; Xie, Yuli; Lu, Senbao
Abstract: As a major driving element of the structure and function of arid and semiarid ecosystems, rainfall is the essential factor limiting plant biological processes. To clarify the characteristics of transpiration and responses to summer rainfall, sap flow density ( F d ) of Pinus tabulaeformis and Hippophae rhamnoides was monitored using thermal dissipation probes. In addition, midday leaf water potential (ψm ) and leaf stomatal conductance ( G s ) were also analyzed to determine water use strategies. The results indicated that the diurnal variation in the normalized F d values exhibited a single‐peak curve for P. tabulaeformis, while H. rhamnoides showed multiple peaks. The normalized F d for P. tabulaeformis remained relatively stable regardless of rainfall events. However, there was also a significant increase in the normalized F d for H. rhamnoides in response to rainfall in June and August ( p  < .05), although no significant differences were observed in July. The normalized F d values for P. tabulaeformis and H. rhamnoides fitted well with the derived variable of transpiration, an integrated index calculated from the vapor pressure deficit and solar radiation ( R s ), using an exponential saturation function. The differences in fitting coefficients suggested that H. rhamnoides showed more sensitivity to summer rainfall ( p  < .01) than P. tabulaeformis . Furthermore, during the study period, P. tabulaeformis reduced G s as soil water decreased, maintaining a relatively constant ψm ; while H. rhamnoides allowed large fluctuations in ψm to maintain G s . Therefore, P. tabulaeformis and H. rhamnoides should be considered isohydric and anisohydric species, respectively. And more consideration should be taken for H. rhamnoides in the afforestation activities and the local plantation management under the context of the frequently seasonal drought in the loess hilly region. Abstract : In this study, we investigated the response to rainfall and the water use strategies of P. tabulaeformis and H. rhamnoides, by measuring F d, ψm, and G s under field conditions. Our aims were to (1) understand the different sap flow responses of these two species to summer rainfall and (2) analyze their patterns of stomatal regulation to identify their water use types.